2022
DOI: 10.2991/assehr.k.220108.115
|View full text |Cite
|
Sign up to set email alerts
|

Excellence Ethnic Characters in Strengthening the Country National Values Identity: An Experience of Indonesia

Abstract: Each country has specific values as the country's identity, which generally lay in the basic description of the country's historical background, socio-cultural conditions, and shared values and dreams. In Indonesia, the values of state identity are inside the Five Fundamental Principles known as Pancasila. As a multicultural country, the contribution of the excellent character of the ethnic groups in Indonesia must strengthen and enrich the values of national identity. However, the power of ethnicity to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Picture 3: Technological scenario of the gamification Table 1 is a SWOT analysis of the selection of RPG Maker MV in making this online gamification. Some targets for the application of character based on ethnic excellence in the learning process (C. Lasambouw et al, 2022) are included in the group of personality development courses (C. M. Lasambouw et al, n.d.) and Pancasila Education (PKn) courses (C. M. Lasambouw & Mathilda, 2020). The local content in question is ten ethnic groups in Indonesia with the largest population, namely ethnic groups: Dayak, Madura, Jawa, Sunda, Baduy, Batak, Banjar, Minahasa, Betawi, Minang (C. M. Lasambouw et al, n.d.), (C. Lasambouw et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Picture 3: Technological scenario of the gamification Table 1 is a SWOT analysis of the selection of RPG Maker MV in making this online gamification. Some targets for the application of character based on ethnic excellence in the learning process (C. Lasambouw et al, 2022) are included in the group of personality development courses (C. M. Lasambouw et al, n.d.) and Pancasila Education (PKn) courses (C. M. Lasambouw & Mathilda, 2020). The local content in question is ten ethnic groups in Indonesia with the largest population, namely ethnic groups: Dayak, Madura, Jawa, Sunda, Baduy, Batak, Banjar, Minahasa, Betawi, Minang (C. M. Lasambouw et al, n.d.), (C. Lasambouw et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Some targets for the application of character based on ethnic excellence in the learning process (C. Lasambouw et al, 2022) are included in the group of personality development courses (C. M. Lasambouw et al, n.d.) and Pancasila Education (PKn) courses (C. M. Lasambouw & Mathilda, 2020). The local content in question is ten ethnic groups in Indonesia with the largest population, namely ethnic groups: Dayak, Madura, Jawa, Sunda, Baduy, Batak, Banjar, Minahasa, Betawi, Minang (C. M. Lasambouw et al, n.d.), (C. Lasambouw et al, 2022). In addition, three tribes (Jawa, Sunda, and Minangkabau) of ten characters in (C. M. The following are the characteristics based on the advantages of 10 ethnic groups in Indonesia (C. M. Lasambouw et al, n.d.), (C. Lasambouw et al, 2022) as shown in table 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 is a SWOT analysis of the selection of RPG Maker MV in making this online gamification. Some targets for the application of character based on ethnic excellence in the learning process [10] are included in the group of personality development courses [6] and Pancasila Education (PKn) courses [11]. The local content in question is ten ethnic groups in Indonesia with the largest population, namely ethnic groups: Dayak, Madura, Jawa, Sunda, Baduy, Batak, Banjar, Minahasa, Betawi, Minang [6], [10].…”
Section: A Qualtitaive-explorativementioning
confidence: 99%